Infochemical use and dietary specialization in parasitoids: a meta‐analysis. Issue 13 (25th May 2017) - van Oudenhove, Louise; Mailleret, Ludovic; Fauvergue, Xavier
Abstract: Many parasitoid species use olfactory cues to locate their hosts. In tritrophic systems, parasitoids of herbivores can exploit the chemical blends emitted by plants in reaction to herbivore‐induced damage, known as herbivore‐induced plant volatiles (HIPVs). In this study, we explored the specificity and innateness of parasitoid responses to HIPVs using a meta‐analysis of data from the literature. Based on the concept of dietary specialization and infochemical use, we hypothesized that (i) specialist parasitoids (i.e., with narrow host ranges) should be attracted to specific HIPV signals, whereas generalist parasitoids (i.e., with broad host ranges) should be attracted to more generic HIPV signals and (ii) specialist parasitoids should innately respond to HIPVs, whereas generalist parasitoids should have to learn to associate HIPVs with host presence. We characterized the responses of 66 parasitoid species based on published studies of parasitoid behavior. Our meta‐analysis showed that (i) as predicted, specialist parasitoids were attracted to more specific signals than were generalist parasitoids but, (ii) contrary to expectations, response innateness depended on a parasitoid's target host life stage rather than on its degree of host specialization: parasitoids of larvae were more likely to show an innate response to HIPVs than were parasitoids of adults. This result changes our understanding of dietary specialization and highlights the need for further theoretical research that will help clarify infochemical use by parasitoids. Abstract : Based on the concept of dietary specialization and infochemical use, we explored the specificity and innateness of parasitoid responses to HIPVs using a meta‐analysis of data from the literature.